Law no. 82/2002 on the protection of the Intellectual property rights with its executive regulations = قانون حماية حقوق الملكية الفكرية ولائحته التنفيذية - Egypt. (2025)
1: Patents for invention and utility designs 1-2:Schematic designs of integrated circuits at-3: Undisclosed data and information IC TE and Industrial Drawings and Designs Part-1: Trade marks and data, and geographical indices Trade Marks and Data. Geographical indices. Part-2: Industrial designs and drawings Author's Rights and Prosomal Rights 29 Beak () Botanical Items 68 Prime Minister's Decree No. 1M6 of the year 2003: Promulgating the executive statutes of books 1, 2, 3 and 4 of the intellectual property rights protection law as promulgated by law No. 82 of the year 2002 96 Letters Patent And Utility Designs And Integrated Circuits Schemata Designs And Undisclosed Information Part-1:Letters patent and utility designs Part-2: Schematic designs of integrated circuits. Part-3: Undisclosed data and information. Table of the due fees concerning the letters patents and utility designs and the schematic designs of integrated circuits. Table of the progressive annual fees effective from the beginning of the second year from the date of submitting the request until the end of the term of protection T- 7212 Trade Marks And Data, The Geographical Indices And The Industrial Drawings And Designs Part-1: Trade marks and data and the geographical indices. Part-2: Industrial drawings and designs.. Table of payable fees concerning trade marks. Table of fees concerning industrial drawings and designs.. 143 191 Book-4 Botanic Items Table of the fee rates on procedures of granting the certificate of 191 grower's right according to article (201) of the law. SLI Book-3 Author's Rights And Related Rights Tables of due fees concerning the author's right and related 176 183 rights